Cognitive and strategic processing of EFL students their effects to the listening skills of EFL students - Mohd Nor, Norzuraina; Lee, Hoi Yeh; Zahari, Nor Sabrina; Ramli, Nur Haslina; Magiman, Mohamad Maulana; Husin, Suraya; Hassan, Norsilawati; Abbas, Mohd Saleh (Society of Psychology and Education, 2022)
While hearing is essential for communication, it is the least studied skill among English as a foreign language student at the national and international levels (EFL). Furthermore, academics and teachers do not always grasp how listening happens, how it can be taught, and how it can be assessed. Our study looked at the listening processes elicited by EFL students when listening for comprehension to fill this need. “A 30-minute multiple-choice listening test, followed by prompted recalls, was performed by twenty-four students.”“Their triggered memory transcriptions, listening notes, and test responses were assessed to see which cognitive processes and approaches they employed while listening and how successful they were as listeners.”“Although people used cognitive processes for listening to both lower and higher levels, most participants, both high and low ability listeners, reported relying on more inefficient lever processes” (word recognition and parsing). Participants often use inferencing, elaboration, and understanding monitoring. Cognitive processes and strategies were triggered in a highly interactive and complex way. “The findings have implications for how effective listening abilities should be taught in the EFL classroom, the type of materials that should be used,” and the most effective techniques for measuring listening skills.